Lifestyle factors associated with benign multiple sclerosis - Guo, Jie; Olsson, Tomas; Hillert, Jan; Alfredsson, Lars; Hedström, Anna Karin (Journal of neurology, neurosurgery and psychiatry, 2025)
BackgroundBenign multiple sclerosis (MS), characterised by minimal disability despite long disease duration, remains poorly understood in terms of its determinants and prognostic implications. While lifestyle factors have been implicated in modifying disease progression, their role in distinguishing benign and non-benign MS remains unclear.MethodsWe conducted a comparative analysis of patients with benign (n=2040) and non-benign MS (n=4283) using data from Swedish nationwide case-control studies with long-term follow-up. Logistic regression models were used to analyse associations between a history of infectious mononucleosis (IM) and lifestyle factors (smoking, body mass index, fish consumption and sun exposure habits) and the likelihood of benign MS. Additionally, Cox regression was used to follow patients with benign MS from the 15-year mark onward, identifying factors associated with the transition to non-benign MS over time.ResultsThe odds of having benign MS were reduced in association with a history of IM (OR 0.54, 95% CI 0.45 to 0.65), adolescent overweight and obesity (OR 0.69, 95% CI 0.56 to 0.85 and 0.46, 95% CI 0.32 to 0.66, respectively) and infrequent fish consumption (OR 0.72, 95% CI 0.60 to 0.88). Similar associations were observed for the risk of transitioning from benign to non-benign MS over time.ConclusionsA history of IM and modifiable lifestyle factors significantly influence the probability of a benign disease course in MS. These findings underscore the potential for targeted lifestyle interventions to improve MS outcomes. Further research is needed to elucidate the mechanisms by which a past IM infection can continue to influence MS progression long after the initial infection.